The Impact of Service Quality and Mobile Banking Usage on Customer Satisfaction at PT Bank Mandiri Kepahiang Branch - Deni Saputra; Neri Susanti; Aji Sudarsono (Journal of Management, Economic, and Accounting, 2026)
As a financial institution, the banking sector naturally requires digital service adaptation, and the banking sector in Indonesia is no exception. Generally, the banking sector in Indonesia comprises two main approaches: conventional banking and Islamic banking. The objective of this study is to determine the influence of service quality and mobile banking usage on customer satisfaction at PT. Bank Mandiri KCP. Kepahiang. The methods used in this study include validity testing, reliability testing, multiple linear regression analysis, the coefficient of determination, and hypothesis testing. This is a quantitative study. The sample size for this study was 55 visitors to Bank Mandiri KCP Kepahiang, selected at random. The results of the multiple linear regression analysis yielded the equation: Y = 8.830 + 0.449X1 + 0.356X2. This indicates a positive regression direction, meaning that the variables Service Quality (X1) and mobile banking usage (X2) have a positive influence on customer satisfaction (Y) at Bank Mandiri KCP Kepahiang. From the calculations using SPSS, the coefficient of determination (R-squared) was found to be 0.689. This means that Service Quality (X1) and Mobile Banking Usage (X2) account for 68.9% of the variation in customer satisfaction (Y), while the remaining 31.1% is influenced by other variables not examined in this study.